National Accounts Statistics: Analysis of Main Aggregates 2022 - United Nations Department of Economic; Social Affairs (United Nations, 2024)
The National Accounts Statistics: Analysis of Main Aggregates, 2022 comprises in the form of analytical tables a summary of the principal national accounting aggregates based on official national accounts data for more than 200 countries and areas, covering the period 1970-2022.